2017
DOI: 10.1177/2309499017739483
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the orientation of lumbar zygapophyseal joints in a South Indian population

Abstract: This study confirms that ZJA is not the same at different levels of the lumbar spine. The mean ZJA progressively increases from L1-L2 to L5-S1. This could explain the greater range of movements in the lumbar spine at the lower levels. The higher prevalence of FT at L4-L5 and L5-S1 seen in this study could explain the greater incidence of disc prolapse and other degenerative disorders at these levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…Previous researchers have used unherniated segments adjacent to the herniated levels as controls [ 1 2 , 15 , 18 , 25 ]. However our study results showed a significant difference in the mean ZJA at different levels of the lumbar spine, similar to those of previous studies [ 5 , 13 , 26 ]. Therefore, we compared the mean ZJA and FT in patients with IVDP at L4–L5 and L5–S1 with corresponding unherniated levels, without using adjacent lumbar levels as controls.…”
Section: Discussionsupporting
confidence: 92%
“…Previous researchers have used unherniated segments adjacent to the herniated levels as controls [ 1 2 , 15 , 18 , 25 ]. However our study results showed a significant difference in the mean ZJA at different levels of the lumbar spine, similar to those of previous studies [ 5 , 13 , 26 ]. Therefore, we compared the mean ZJA and FT in patients with IVDP at L4–L5 and L5–S1 with corresponding unherniated levels, without using adjacent lumbar levels as controls.…”
Section: Discussionsupporting
confidence: 92%
“…There is currently no universal consensus about the consideration of clinically significant LFJT. Hence, LFJs angulation may normally vary from 5 to 10 degrees Authors concluded that these results may offer an explanation for the more frequent occurrence of lumbar disc herniation and related degenerative disorders as lumbar arthrosis and degenerative spondylolisthesis encountered at these levels [23]. This thesis has been also adopted from other studies in recent literature [3,14,26].…”
Section: Lfjs Tropism (Lfjt)mentioning
confidence: 89%
“…The three-dimensional LFJs and the anteriorly located intervertebral disc at each lumbar spine level compose an anatomic entity described as spinal segment, "three-joint complex" or articular triad [15,16,21,23,26,32,38]. These articular structures are theorized to constitute a single unit since the emergence of degenerative alterations in one joint has a subsequent influence on the biomechanic behavior of the whole unit [26].…”
Section: Biomechanical Datamentioning
confidence: 99%
“…other causes of low backache include abnormal orientation of joints (Mohanty et al, 2017). Many cases of spinal canal stenosis have found to have some relation with the anatomical differences.…”
Section: Introductionmentioning
confidence: 99%